Behaviour of RC slabs flexurally strengthened with prestressed NSM CFRP laminates - Hosseini, Mhoammadreza Mostakhdemin (2013)
To investigate the effect of the prestressed NSM CFRP laminates on the behaviour of RC slabs, an experimental program was carried out. A total of four RC slabs were tested, a reference slab (without CFRP), and three slabs flexurally strengthened using NSM CFRP laminates with different prestress level: 0%, 20% and 40% of the ultimate tensile strength of the CFRP material. The experimental program is described and the main results are presented and analyzed in terms of the structural behaviour of the RC slabs, failure modes and performance of the NSM technique with prestressed CFRP laminates.